A National Comparison of Postoperative Outcomes in Completion Thyroidectomy and Total Thyroidectomy. (March 2021) - Brauer, Philip R.; Reddy, Chandana A.; Burkey, Brian B.; Lamarre, Eric D.
Objective: To characterize and assess the non–thyroid-specific postoperative complications of completion thyroidectomy as compared with total thyroidectomy. Study Design: Retrospective analysis: 2005 to 2017. Setting: National Surgical Quality Improvement Program database. Subjects and Methods: Patients aged >18 years receiving a completion or total thyroidectomy were eligible for inclusion. Patients not treated by otolaryngologists or general surgeons and with unknown demographic variables were excluded. Results: A total of 70, 638 patients were analyzed, representing 64, 763 total thyroidectomies and 5875 completion thyroidectomies. The 30-day mortality rate was 0.1% for both procedures ( P > .05). Overall, 1.7% and 1.4% of patients undergoing total and completion thyroidectomies experienced at least 1 complication ( P > .05), while 1.2% and 0.9% had a postoperative medical complication ( P = .0186), respectively. On multivariable analysis, patients undergoing total thyroidectomies were significantly more likely to return to the operating room (odds ratio [OR], 1.36; 95% CI, 1.04-1.80; P = .027) and to be readmitted (OR, 1.45; 95% CI, 1.16-1.81; P = .001). Adjusted analysis also demonstrated that patients undergoing total thyroidectomies were more likely to be inpatients (OR, 1.17; 95% CI, 1.11-1.24; P < .001), be treated by nonotolaryngologists (OR, 1.36; 95% CI, 1.29-1.45; P < .001), and smoke (OR, 1.22; 95% CI, 1.13-1.33; P < .001). Conclusion: National data suggest that total and completion thyroidectomies are relatively safe procedures but that completion thyroidectomies are associated with lower rates of postoperative complications. These findings may play a role in determining treatment plans for patients and optimizing risk reduction.